Disrupted lives : how people create meaning in a chaotic world - Becker, Gaylene (University of California Press, 1997)
Our lives are full of disruptions, from the minor - a flat tire, an unexpected phone call - to the fateful - a diagnosis of infertility, an illness, the death of a loved one. And the ways in which we come to understand and cope with these disruptions can say as much about our cultural heritage as they say about us as individuals. In the first book to examine disruption in American life from a cultural rather than a psychological perspective, Gay Becker follows hundreds of people to find out what they do after something unexpected occurs. Starting with bodily distress, she shows how individuals recount experiences of disruption metaphorically, drawing on important cultural themes to help them reestablish order and continuity in their lives. Through the vivid and poignant stories of people from different walks of life who experience different types of disruptions, Becker examines how people rework their ideas about themselves and their worlds, from the meaning of disruption to the meaning of life itself.